2005
DOI: 10.1091/mbc.e05-05-0410
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of N-Cadherin-associated Cortactin by Fer Kinase Regulates N-Cadherin Mobility and Intercellular Adhesion Strength

Abstract: Cortactin regulates the strength of nascent N-cadherin-mediated intercellular adhesions through a tyrosine phosphorylation-dependent mechanism. Currently, the functional significance of cortactin phosphorylation and the kinases responsible for the regulation of adhesion strength are not defined. We show that the nonreceptor tyrosine kinase Fer phosphorylates cadherin-associated cortactin and that this process is involved in mediating intercellular adhesion strength. In wild-type fibroblasts N-cadherin ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 47 publications
(58 reference statements)
4
52
0
Order By: Relevance
“…22 In line with this finding, a rapid increase in Rac1 activity upon VE-cadherin homotypic adhesion was detected biochemically, which was induced using beads coated with the VE-cadherin ectodomain. Thus, as was shown for E-, M-and N-cadherin, [64][65][66][67] we showed that VEcadherin can signal in an outside-in fashion to activate Rac1, providing a bidirectional feedback mechanism. 22 Of note, ongoing local remodeling of cell-cell junctions is observed even in apparently stable endothelial monolayers.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasessupporting
confidence: 76%
“…22 In line with this finding, a rapid increase in Rac1 activity upon VE-cadherin homotypic adhesion was detected biochemically, which was induced using beads coated with the VE-cadherin ectodomain. Thus, as was shown for E-, M-and N-cadherin, [64][65][66][67] we showed that VEcadherin can signal in an outside-in fashion to activate Rac1, providing a bidirectional feedback mechanism. 22 Of note, ongoing local remodeling of cell-cell junctions is observed even in apparently stable endothelial monolayers.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasessupporting
confidence: 76%
“…The variations in binding intensity that arise in SYF and SYF +/+ cells expressing Src527F indicate a fundamental mechanistic difference in the concentration of phosphotyrosine binding sites for several SH2-domain-containing proteins that are likely to have key roles in invadopodia maturation. Interestingly, tyrosine-phosphorylated cortactin is known to interact with several high-intensity 'hits', including Arg, Abl (Boyle et al, 2007), Fer (El Sayegh et al, 2005), Crk (Bougneres et al, 2004) and Nck (Tehrani et al, 2007), consistent with its role in invadopodia maturation. Experiments to elucidate additional proteins involved in these signaling complexes are currently underway.…”
Section: Cells Forming Pre-and Mature Invadopodia Have Distinct Phospmentioning
confidence: 76%
“…It should be noted, however, that many non-specific manuevers that inhibit endocytosis can influence cadherin function by alternative mechanisms. For example, hypertonic stress induces tyrosine phosphorylation of cortactin [22], which contributes to cadherin junction integrity [23,24] (Helwani et al, unpublished). These disparate models thus remain to be resolved and warrant further investigation.…”
Section: Regulating Internalisation: the Yin And Yang Of Adhesion Andmentioning
confidence: 99%